Going regional: Community-based regionalism, transportation, and local hiring agreements - Todd Swanstrom; Brian Banks (University of California, Institute of Urban and Regional Development (IURD), 2007)
Community-based regionalism (CBR) is the attempt by community-based organizations (CBOs) to reorient regional policies to benefit disadvantaged communities. Advocates of CBR have mostly called not for regional governments but for collaborative regional governance processes. This article examines the efforts of (CBOs) to form regional governance processes that target jobs from federally funded transportation projects to disadvantaged communities. Transportation policy has long been dominated by a policy monopoly centered on state departments of transportation and their highway engineers. By balancing conflict and collaboration, entrepreneurial CBOs have been able to penetrate this policy monopoly and negotiate successful local hiring agreements using collaborative regional governance processes. We conclude that success will be limited, however, without supportive federal and state policies.
Keywords: 330